IMPLEMENTATION OF THE HEALTHY INDONESIA PROGRAM WITH A FAMILY APPROACH (PIS-PK) AT COMMUNITY HEALTH CENTERS IN BINTAN DISTRICT, KEPULAUAN RIAU PROVINCE - Bisri, Moh (International Journal of Social Science, 2023)
One of the policies to strengthen quality essential health efforts is through the Healthy Indonesia Program with a Family Approach (PIS-PK), monitoring and evaluating policies to measure whether policy implementation is going according to the expected goals. This study's purpose was to implement the Healthy Indonesia Program with a Family Approach (PIS-PK) at the Bintan District Health Center. This study uses a qualitative design, determining informants by purposive sampling technique where the primary informants are five people, and triangulation informants are six. Data analysis uses content analysis. The results of the PIS-PK implementation research could have been more optimal. The factors that support implementation are the communication factors that have gone well with the internal and external socialization and the attitude factor of the implementer committing enough to support the program's implementation well. While the inhibiting factors in terms of resources are limited resources, program infrastructure, and delays in budget disbursement. From the bureaucratic structure factor, there needs to be tiered coordination between the health office and the puskesmas. The district health office can immediately create a program organizational structure to facilitate coordination, facilitate the budget disbursement process and provide program support infrastructure. There needs to be cross-sectoral collaboration in supporting the implementation of PIS-PK at the Bintan District Health Center